(untitled) (Khairulummah, 2025)
This paper presents a study of the role of women in the development of Islamic jurisprudence, particularly in the context of the Hanafi and Shafi‘i eras. While the history of fiqh is usually attributed to male jurists, historical evidence shows that women were also active in teaching, transmitting hadith, offering juristic opinions, and participating in scholarly circles. In the Hanafi period, women appeared not only as transmitters of hadith and teachers but also as guides in legal matters. Similarly, in the Shafi‘i era, many female scholars attained mastery in both fiqh and hadith, and even taught well-known male scholars. They played a vital role in strengthening the scholarly tradition by teaching in mosques, madrasas, and private circles. Their contributions had two prominent aspects: intellectually, women expanded the juristic heritage and safeguarded its authenticity; and socially, their scholarly presence highlighted the importance of women’s education. This research makes it clear that women’s role in the formation and growth of Islamic jurisprudence was not marginal but central. Their contributions remain a shining example for promoting women’s participation in scholarly and juristic fields today.